Posterior Shoulder Instability but Not Anterior Shoulder Instability Is Related to Glenoid Version - Thomas K. Moore, M.B., B.Ch., M.Ch; Conor J. Kilkenny, M.B., B.Ch; Eoghan T. Hurley, M.B., B.Ch., M.Ch., Ph.D; Bryan M. Magee, B.Sc; Jay M. Levin, M.D; Sami U. Khan, F.R.C.S; Jonathan F. Dickens, M.D; Hannan Mullett, F.R.C.S (Elsevier, 2023)
Purpose: To assess and compare glenoid version in patients with anterior shoulder instability (ASI), posterior shoulder instability (PSI), and a control group. Methods: The operative notes of all patients that had undergone arthroscopic shoulder instability repair between January 2017 and May 2022 were retrospectively reviewed. Magnetic resonance imaging scans were then analyzed, and glenoid version was measured by a single blinded observer. A P value <.05 was considered statistically significant. Results: There were 100 patients included in the ASI group, 65 in PSI group, and 100 in the control group. The mean glenoid versions for the ASI group were −16°, −9.1°, and −9.2° for the vault version, simplified vault version, and chondrolabral version, respectively. The mean glenoid versions for the PSI group were −21°, −13.4°, and −16.6° for the vault version, simplified vault version, and chondrolabral version, respectively. The mean versions for the control group were −17.8°, −9.5°, and −9.8° for the vault version, simplified vault version and chondrolabral version, respectively. ANOVA testing and post hoc comparisons revealed the PSI group to be significantly more retroverted than both other groups P < .001. The ASI group's degree of glenoid version was not significantly different to that of the control P = .009. Conclusion: Patients with PSI have a higher degree of retroversion in comparison to those with ASI and control. There is no significant difference in glenoid version among patients with ASI when compared with control. Level of Evidence: Level III, retrospective comparative study.